Aduncothrips newly recorded from China, with three new species and a new generic synonym (Thysanoptera: Aeolothripidae) - Li, Yajin; Elie, Ntirenganya; Liu, Hui; Zhang, Hongrui (Zootaxa, 2022)
The previously monotypic genus Aduncothrips Ananthakrishnan from India is newly recorded from China with three new species: A. albus sp. n., A. huapingensis sp. n., A. kailiensis sp. n. The genus Desmidothrips Mound from Australia is synonymized with Aduncothrips, and the Japanese species A. japonicus (Masumoto & Okajima) is newly recorded in China with first description of the male. A key to the seven known species of Aduncothrips is provided. Males in this genus, where known, have maxillary palps 3-segmented with segment II undivided, and tergite IX without claspers.